PENDIDIKAN SUFISTIK SAID NURSI DAN IMAM AL-GHAZALI; SOLUSI NON MEDIS DI MASA PANDEMIC - Saepul Bahri (QATHRUNÂ, 2021)
The goal desired by the authors in this study is to provide non-medical solutions in the form of mental therapy for educational institutions and humans involved in education so that they feel calm, patient, and have confidence in themselves, namely avoiding the Covid 19 pandemic. The methodology used is library research, namely by collecting literature in the form of works in the form of books, journals, papers, from 2 Sufi figures Said Nursi and Imam Al-Ghazali. The method used is qualitative with a comparative study of the thoughts of the two figures (Said Nursi and Imam Al-Ghazali) then a synthesis is carried out to find differences, similarities and common ground between the two Sufi figures. The methods, properties and steps offered by Said Nursi and Imam Al-Ghazali are able to break the chain of spreading the Covid-19 pandemic if done properly and correctly. Said Nursi and Imam Al-Ghazali gave their spiritual knowledge about the purification of the soul so that life is more directed, meaningful and dignified. Of course, humans have problems by nature, but stupid humans are those who let their problems pile up, and see problems as burdens and suffering. The concepts of Al-Lathaif al-Asyr and Tazkiyah al-Nafs provide understanding and knowledge to humans about the true nature of humans.